Peran E-Voting Dalam Mendobrak Batasan Tradisional Sebagai Upaya Menyongsong Pemilu Modern - Hilyatul Asfia (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
The purpose of this research is to analyze how the application of Electronic Voting in the General Elections in Indonesia is a step toward modernizing the country’s electoral system. E-Voting has been used by several countries including Brazil, India, Switzerland, and Australia, with a positive response from society. At least several e-voting methods can be selected and implemented in Indonesia based on the characteristics of the people and the regions. Based on this research, it is known that e-voting complies with the Indonesian legal framework, including Law Number 11 of 2008 on Electronic Information and Transactions, Article 85 of the Regional Head Election Law, and the Constitutional Court Decision No. 147/PUU-VII/2009. This study is socio-legal research with qualitative and quantitative analysis. Evaluation of statutory performance is carried out materially (substance, discrepancy, and implementation of regulations) which is measured based on statutory approaches. According to research on the potential benefits of implementing e-voting, increasing the efficiency and speed of vote counting, reducing human error and saving time and resources, increasing participation, and increasing transparency and accountability in the general election process through technology that can ensure the integrity of voting are all advantages of implementing e-voting.